Beyond intersubjectivity in olfactory psychophysics I: Troubles with the Subject - Alač, Morana (Social studies of science, 2020)
This article provides an experience-oriented relational account that goes beyond a human control of the world. Rather than working with the notion of intersubjectivity (commonly evoked in sensory STS, and still conserving the subject/object opposition), the article reports on how the sense of smell affords a rethinking of our relationship with the world. It does so by challenging the assumption of olfactory ineffability as it turns to a place whose inhabitants speak about smell as a part of their everyday affairs: a laboratory of olfactory psychophysics. There, we attend to a multimodal, embodied language that participates in preparing, running and analyzing scientific experiments. While Western languages are short on specialized vocabulary for expressing olfactory qualities and it feels difficult to talk about smell, laboratory events manifest smell language in its enmeshing with the sensory realm and the world. Noticing these ties destabilizes the idea of agential subject, highlighting instead our pre-intentional sensibility, in its connection with the world. A sister article on ‘troubles with the Object’ (Alač, 2020) continues to argue that the notion of intersubjectivity is overly narrow, highlighting our immersion in the world (rather than assuming our dominance of it).